Receptor targeting drug delivery strategies and prospects in the treatment of rheumatoid arthritis - Jaber Emami; Zahra Ansarypour (Wolters Kluwer Medknow Publications, 2019)
Rheumatoid arthritis (RA), a chronic inflammatory disease, is characterized by cartilage damage, bone tissue destruction, morphological changes in synovial fluids, and synovial joint inflammation. The inflamed synovial tissue has potential for passive and active targeting because of enhanced permeability and retention effect and the existence of RA synovial macrophages and fibroblasts that selectively express surface receptors such as folate receptor β, CD44 and integrin αVβ. Although there are numerous interventions in RA treatment, they are not safe and effective. Therefore, it is important to develop new drug or drug delivery systems that specifically targets inflamed/swollen joints but attenuates other possible damages to healthy tissues. Recently some receptors such as toll-like receptors (TLRs), the nucleotide-binding oligomerization domain-like receptors, and Fc-γ receptor have been identified in synovial tissue and immune cells that are involved in induction or suppression of arthritis. Analysis of the TLR pathway has moreover suggested new insights into the pathogenesis of RA. In the present paper, we have reviewed drug delivery strategies based on receptor targeting with novel ligand-anchored carriers exploiting CD44, folate and integrin αVβ as well as TLRs expressed on synovial monocytes and macrophages and antigen presenting cells, for possible active targeting in RA. TLRs could not only open a new horizon for developing new drugs but also their antagonists or humanized monoclonal antibodies that block TLRS specially TLR4 and TLR9 signaling could be used as targeting agents to antigen presenting cells and dendritic cells. As a conclusion, common conventional receptors and multifunctional ligands that arte involved in targeting receptors or developing nanocarriers with appropriate ligands for TLRs can provide profoundly targeting drug delivery systems for the effective treatment of RA.